Analysis of Interest Factors in Reading THE MAN Library 10 Jombang - Arjuna Pratama; Moh Faridl Darmawan (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Minat reading is the desire or tendency of the heart to read. It is also stated by Saepudin that the interest in reading is a tendency of the soul that encourages someone to do something about reading. Based on Culture and Tradition, reading is a common thing done by humans so that reading is considered a trivial thing to do. Therefore, researchers want to analyze the library reading interest factor in MAN 10 Jombang. In research researchers use qualitative research with data collection procedures through observation, interview and documentation. And the results show that there are several supporting factors and obstacles that affect students in reading these factors can be through teachers, friends and the environment, but the teacher's efforts to increase students' reading interest also continue to be implemented one of the efforts he does is to add existing facilities in the library that can attract students to go to the library and increase students' reading interest.